FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN DOKTER TERHADAP PERESEPAN OBAT GENERIK DI INSTALASI FARMASI RSUD dr. R. GOETENG TAROENADIBRATA PURBALINGGA - Gangga Harima; Soedarso -; Anjar Mahardian K (Media Farmasi Indonesia, 2013)
Permenkes RI No. HK.02.02/Menkes/068/2010 dispute that any mandatory to use generic drugs in public health facility. Recently, The Indonesian generic is have to using low, however the price is cheaper. The objective of this research to is determinate the pecentage of doctor’s obedience to generic prescription and know the influance of knowladge, trust, generic drugs avaluable and patient’s influance to the obedience of docter’s to prescribe generic drugs in Farmacy Instalation of RSUD dr. R. Goeteng Taroenadibrata Purbalingga. The research was observational research, used cross sectional approach and retrospective data. The instrument of research is quisioner. Validity test used to know validitas of quisioner. Statistic analysis are used bivariat analysis with chi square test and multivariat analysis used regresion logistic test. The result showed the percentage of doctor’ obedient was 58.3% and the unobedience 41.7%. Knowladge factor, trust, avaluability of drugs and patient influance each of them had significant influance to the level of doctor’s obedience to used generic drug’s. P value < 0.05. Factors of Knowladge, trust, avaluable of drugs and patient influance simultan had significant influance to the obedience of doctor. The conclution of this research is the persentage of doctor who obedience with generic prescribing were 58.3%. The other side the pertsentage of doctor who inobedience with generic prescribing were 41.7%. The higher of knowladge, trust, generic drugs avaluable and patient’s influance, so the higher of obedience of doctor in generic prescribe.